2008
DOI: 10.1097/brs.0b013e31817b5bcf
|View full text |Cite
|
Sign up to set email alerts
|

Head-Turned Postures Increase the Risk of Cervical Facet Capsule Injury During Whiplash

Abstract: Compared to previously-reported data for these specimens, peak capsule strains with a pretorque were double those without a pretorque (17% +/- 6%) and not significantly different from those at partial failure of the ligament (35% +/- 21%). Thus a head-turned posture increases facet capsular ligament strain compared to a neutral head posture-a finding consistent with the greater symptom severity and duration observed in whiplash patients who have their head turned at impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…An earlier study addressed the issue of increased injury susceptibility with head rotation using PMHS motion segments and quasi-static shear loads [37]. That study identified a two-fold increase in ligament strains with 1.5 Nm axial pretorque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study addressed the issue of increased injury susceptibility with head rotation using PMHS motion segments and quasi-static shear loads [37]. That study identified a two-fold increase in ligament strains with 1.5 Nm axial pretorque.…”
Section: Discussionmentioning
confidence: 99%
“…However, injuries to those structures are not likely responsible for the most commonly reported chronic whiplash-related symptoms including posterior neck pain and suboccipital headache. One experimental investigation into the effects of axial rotation on capsular ligament strains in posteriorly directed loading determined increased strains in axially rotated joints [37]. However, that study incorporated static loading of isolated cervical motion segments that does not recreate inertial loading of the head-neck complex during dynamic impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Maak et al (2006) found that "the dynamic strains of the alar, transverse, and apical ligaments during impact did not exceed the corresponding non-injurious baseline values" while Siegmund et al (2008) reported that an axial rotation "doubles the MPS in the capsular ligament compared to the neutral posture". They also found that capsular strains during the simulated whiplash exposure with the head turned were not significantly different from the maximum principal strain (MPS) associated with partial failure of the capsule.…”
Section: Introductionmentioning
confidence: 99%
“…8 At the same time, biomechanical studies have shown that the direction of the impact, muscle activity (preparation) at the time of impact, 9 existing neck disease, 10 and posture 11 can influence the forces at play on different cervical structures. Therefore, simplistic assessments of susceptibility or likelihood of injury based on speed of impact are unlikely to be valid.…”
mentioning
confidence: 99%